NMR study of the antifreeze activities of active and inactive isoforms of a type III antifreeze protein. Issue 23 (23rd October 2016) - Choi, Seo‐Ree; Seo, Yeo‐Jin; Kim, Minjae; Eo, Yumi; Ahn, Hee‐Chul; Lee, Ae‐Ree; Park, Chin‐Ju; Ryu, Kyoung‐Seok; Cheong, Hae‐Kap; Lee, Shim Sung; Jin, EonSeon; Lee, Joon‐Hwa
Abstract : The quaternary‐amino‐ethyl 1 (QAE1) isoforms of type III antifreeze proteins (AFPs) prevent the growth of ice crystals within organisms living in polar regions. We determined the antifreeze activity of wild‐type and mutant constructs of the Japanese notched‐fin eelpout ( Zoarces elongates Kner ) AFP8 (nfeAFP8) and characterized the structural and dynamics properties of their ice‐binding surface using NMR. We found that the three constructs containing the V20G mutation were incapable of stopping the growth of ice crystals and exhibited structural changes, as well as increased conformational flexibility, in the first 310 helix (residues 18–22) of the sequence. Our results suggest that the inactive nfeAFP8s are incapable of anchoring water molecules due to the unusual and flexible backbone conformation of their primary prism plane‐binding surface. Abstract :